Long-term Follow up of Patients with Acute Aortic Syndromes: Relevance of both Aortic and Non-aortic Events. (August 2018) - Corsini, Anna; Pacini, Davide; Lovato, Luigi; Russo, Vincenzo; Lorenzini, Massimiliano; Foà, Alberto; Leone, Ornella; Nanni, Samuele; Mingardi, Francesca; Reggiani, Letizia Bacchi; Melandri, Giovanni; Di Bartolomeo, Roberto; et al.
Abstract : Background: The aim was to assess the long-term outcome of patients diagnosed with type A and type B acute aortic syndromes (AAS) and the mortality risk predictors. Methods: A single centre retrospective observational study was performed on consecutive patients diagnosed with AAS and discharged between 2000 and 2016: 242 surgically treated type A, 87 uncomplicated, medically treated type B, and 80 complicated type B who received endovascular/surgical/hybrid treatment. Follow up of discharged patients (5 ± 3.9 years) was almost complete by the end of the study (December 2017). Results: The mean age was 65.3 ± 12.5 years, and 70.2% were men. Long-term all cause mortality was 5.4 per 100 patients per year in surgically treated type A AAS patients and 6.7 per 100 patients per year in type B AAS patients (p = .236). The rates of major aorta related events were 6.1 per 100 patients per year and 13.4 per 100 patients per year, respectively (p < .001). Non-aorta related events during long-term follow up occurred in 18.2 per 100 patients per year in type A and 13.8 per 100 patients per year in type B (p = .055). At the end of follow up 279/409 (68.2%) patients (165/242 type A and 114/167 type B) experienced at least one event. Conclusions: Among patients with either type A or type B AAS surviving the acute phase, the risk of adverse aorta and non-aorta related events, including death, persists during follow up, so that eventually two thirds of patients will experience at least one event. Notably, all cause mortality after type B AAS exceeds that of type A AAS after three years.